Post and Core Treatment of Maxillary Right Central Incisor Using a Fibre Post: A Case Report - Jnana Ranjan Swain1 , Sushant Mohanty2 , Sonu Acharya3 , Bismay Singh4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Preserving a badly mutilated tooth has always been a challenge for the dentist. Patients usually approach toa dentist where there is significant loss in tooth structure. Post and core can be done in such a case for therestoration of the teeth. For success in such cases, proper post-selection is of utmost importance. This casereport highlights the usage of post and core to save teeth with less crown structure using prefabricated fiberposts.